Analisis Reaksi Pasar Sebelum dan Selama Isu Geopolitik di Eropa - Luntungan, Deilamy Nigel; Mawikere, Lidia; Mintalangi, Syermi (E-Jurnal Akuntansi; Vol 34 No 4 (2024), 2024)
Various events occurring in the world have had an impact on the capital market. One of these events is the Russian geopolitical invasion of Ukraine on February 24 2022. The aim of this research is to determine the influence of geopolitical dynamics in Europe on the market capitalization of energy sector companies. The observation period was carried out 1 quarter before the incident and 3 quarters during the incident. This type of research is quantitative research with a descriptive approach. The sampling method used was purposive sampling with 52 companies as samples. Data analysis took the form of a Wilcoxon Sign Rank difference test using IBM SPSS 26. The results of this research were that there was a significant difference in market capitalization in the 2 periods before and during the geopolitical issue in Europe, and there was no significant difference in market capitalization in 1 period during the geopolitical issue in Europe.  Keywords: Market Performance; Russian Invasion of Ukraine; Market Capitalization